Analyse algébrique d’un probléme de Dirichlet non linéaire et singulier - Marti, Jean-Andre; Nuiro, Silvère P. (Topological Methods in Nonlinear Analysis, 1999)
The algebraic structure of a factor ring and the topological structure of a semi-normed algebra permit the construction of many algebras of generalized functions. Some of them are well suitable to solve a non linear Dirichlet problem with irregular data.